2020
DOI: 10.1038/s41598-020-79109-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting oxytocin receptor (Oxtr)-expressing neurons in the lateral septum to restore social novelty in autism spectrum disorder mouse models

Abstract: Autism spectrum disorder (ASD) is a continuum of neurodevelopmental disorders and needs new therapeutic approaches. Recently, oxytocin (OXT) showed potential as the first anti-ASD drug. Many reports have described the efficacy of intranasal OXT therapy to improve the core symptoms of patients with ASD; however, the underlying neurobiological mechanism remains unknown. The OXT/oxytocin receptor (OXTR) system, through the lateral septum (LS), contributes to social behavior, which is disrupted in ASD. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…We assessed the expression of genes involved in neurotransmission ( Figure 3 ; n = 8 animals per group, four independent experiments), such as the dopamine receptors (DRD1 and DRD2) and the DA responsive protein DARPP32, the serotonin receptors (5HTR1A and 5HTR2A) and the serotonin transporter 5HTT, and genes involved in synaptic plasticity coding for the NMDA subunits (GRIN2A and GRIN2B), and CREB1. We also measured the expression levels of the mesotocin receptor (OXTR), the avian homolog of oxytocin, since the lateral part of the septum is known to receive consistent oxytocinergic innervation ( Loveland et al, 2019 ; Horiai et al, 2020 ). We again used linear mixed models to evaluate the effect of treatment (CTRL vs. VPA) and transcripts, and found that the best fitting model was a random slopes and intercepts model with the same parameters used for analysis of gene expression in the mesencephalon.…”
Section: Resultsmentioning
confidence: 99%
“…We assessed the expression of genes involved in neurotransmission ( Figure 3 ; n = 8 animals per group, four independent experiments), such as the dopamine receptors (DRD1 and DRD2) and the DA responsive protein DARPP32, the serotonin receptors (5HTR1A and 5HTR2A) and the serotonin transporter 5HTT, and genes involved in synaptic plasticity coding for the NMDA subunits (GRIN2A and GRIN2B), and CREB1. We also measured the expression levels of the mesotocin receptor (OXTR), the avian homolog of oxytocin, since the lateral part of the septum is known to receive consistent oxytocinergic innervation ( Loveland et al, 2019 ; Horiai et al, 2020 ). We again used linear mixed models to evaluate the effect of treatment (CTRL vs. VPA) and transcripts, and found that the best fitting model was a random slopes and intercepts model with the same parameters used for analysis of gene expression in the mesencephalon.…”
Section: Resultsmentioning
confidence: 99%
“…3; n = 8 animals per group, four independent experiments), like the dopamine receptors (DRD1 and DRD2) together with the DA responsive protein DARPP32, the serotonin receptors (5HTR1A and 5HTR2A) with the serotonin transporter 5HTT and genes involved in synaptic plasticity coding for the NMDA subunits (GRIN2A and GRIN2B), and CREB1. We also measured the expression levels of the mesotocin receptor (OXTR) the avian homolog of oxytocin, since the lateral part of the septum is known to receive consistent oxytocinergic innervation (Loveland et al, 2019;Horiai et al, 2020). We again used linear mixed models to evaluate the effect of treatment (CTRL vs VPA), DA subgroup (SN vs VPA) and transcripts, and found that the best fitting model was a random slopes and intercepts model with the same parameters used for analysis of gene expression in the mesencephalon.…”
Section: Resultsmentioning
confidence: 99%
“…The higher amounts of OXT will help to improve facial processing and human interpersonal contact, causing milder symptoms of ASD. A recent mouse ASD model study has demonstrated that targeting OXTR-expressing neurons in the lateral septum restores social skills [ 31 ]. Both our current study and previous research [ 27 , 31 ] suggest that OXT is adaptive and can restore the homeostasis in the body.…”
Section: Discussionmentioning
confidence: 99%